Do information publicity and moral norms trigger waste-sorting intention among households? A sequential mediation analysis - Li, Yan; Bhutto, Muhammad Yaseen; Sun, Chaojing; Mehdi, Syed Muntazir (Frontiers in Psychology, 2023)
The quick pace of technological advancement and urbanization has led to significant increase in waste production, which has severly damaged environment quality and human health. The sorting of waste is a viable way to reduce environmental hazards and attain high recovery rates in the cities. This research extended the theory of planned behavior (TPB) by integrating information publicity (IP) and moral norms (MN). A conceptual model has been developed to explore the predictors of waste sorting intention of the houesholds. The data from 361 Pakistani households have been collected using the purposive sampling method and analyzed via Partial least square structural equation modeling (PLS-SEM). The results of direct and indirect relationship revealed that the proposed model significantly contributes to waste sorting intention. The results also validates that MN and TPB constructs attitude (ATD), subjective norms (SN), and perceived behavioral control (PBC) sequentially mediates between IP and WSI. However, the positive impact of information publicity on perceived behavioral control was insignificant. The current study contributes to the TPB and enriches the environmental management literature. Further, the study's findings provide helpful, practical implications to practitioners and academicians that help reduce environmental pollution.